Alteration in body water compartments following intermittent fasting in Ramadan - Najafi, Mohammad Taghi; Sadoogh Abbasian, Ali; Mohammadi, Hamed; Abbasi, Mohammad Reza; Khatami, Mohammad Reza; Ghafari, Ali; Shojamoradi, Mohammad Hossein (Frontiers in Nutrition, 2023)
Concerning the health outcomes of intermittent fasting in Ramadan, loss of fat-free mass (FFM) and changes in the content of body water are of paramount importance. In this study, we aimed to assess the concomitant alterations in body water compartment and composition following Ramadan fasting in healthy individuals. We conducted an open-label cohort with longitudinal follow-up, involving 73 healthy medical staff who planned to fast for at least 20 consecutive days during Ramadan. The primary outcomes of the cohort were changes in parameters related to body composition and water content, which were measured using bioelectrical impedance analysis by InBody S10 (InBody, Seoul, South Korea). Based on the results, the participants' weight decreased significantly by approximately 1,030 g after the fasting period (P<0.001). There was a significant reduction in the fat mass of an average 828 g (P<0.001), which accounted for more than 80% of the weight loss. The decline in FFM was not significant (190 g; P=0.234). The amount of total body water (TBW) and extracellular water (ECW) did not change, while intracellular water (ICW) decreased significantly by about 160 mL (P=0.027). A strong correlation was observed between the reduction of phase angle and the increase in ECW/TBW ratio (R=-0.71, P<0.001). Overall, our findings revealed a minimal amount of weight loss after Ramadan fasting, which was mainly due to the loss of fat mass. The parallel decrease in ICW and phase angle indicated impaired cell membrane integrity, with subsequent movement of water from the intracellular to the extracellular compartment.